2023
DOI: 10.3390/cells12182243
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Dependent Attenuation of Pro-Fibrotic Responses after Cannabigerol Exposure in Primary Rat Hepatocytes Cultured in Palmitate and Fructose Media

Klaudia Sztolsztener,
Karolina Konstantynowicz-Nowicka,
Anna Pędzińska-Betiuk
et al.

Abstract: Hepatic fibrosis is a consequence of liver injuries, in which the overproduction and progressive accumulation of extracellular matrix (ECM) components with the simultaneous failure of matrix turnover mechanisms are observed. The aim of this study was to investigate the concentration-dependent influence of cannabigerol (CBG, Cannabis sativa L. component) on ECM composition with respect to transforming growth factor beta 1 (TGF-β1) changes in primary hepatocytes with fibrotic changes induced by palmitate and fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Regardless of the assessment of the impact of the tested phytocannabinoids on proteins of the redox system and those involved in the development of inflammation, the response of collagen was also checked, which was an example of a protein on which the phytocannabinoids had both protective and regenerative effects. It has been found that, under the control conditions, CBG slightly increases collagen expression in both fibroblasts and keratinocytes, which may be related to the effect of CBG on collagen-degrading enzymes, including the stimulation of metalloproteinases [ 83 ]. However, the oxidative stress and proinflammatory conditions induced by the UVA radiation clearly inhibit collagen biosynthesis through various mechanisms [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the assessment of the impact of the tested phytocannabinoids on proteins of the redox system and those involved in the development of inflammation, the response of collagen was also checked, which was an example of a protein on which the phytocannabinoids had both protective and regenerative effects. It has been found that, under the control conditions, CBG slightly increases collagen expression in both fibroblasts and keratinocytes, which may be related to the effect of CBG on collagen-degrading enzymes, including the stimulation of metalloproteinases [ 83 ]. However, the oxidative stress and proinflammatory conditions induced by the UVA radiation clearly inhibit collagen biosynthesis through various mechanisms [ 84 ].…”
Section: Discussionmentioning
confidence: 99%